Escherichia coli ST302: Genomic Analysis of Virulence Potential and Antimicrobial Resistance Mediated by Mobile Genetic Elements - Jarocki, Veronica M.; Reid, Cameron J.; Chapman, Toni A.; Djordjevic, Steven P. (Frontiers in Microbiology, 2020)
aEPEC are associated with persistent diarrhea, and diarrheal outbreaks in both humans and animals worldwide. They are differentiated from typical EPEC by the lack of bundle-forming pili, and from EHEC by the lack of phage-mediated stx toxins. However, phylogenetic analyses often associate aEPEC with EHEC, promoting the hypothesis that aEPEC are the progenitors of EHEC, which is supported by aEPEC conversion to EHEC by stx¬-carrying phages. While aEPEC can cause disease outright, the potential to acquire stx, one of the most potent bacterial toxins known, merits close monitoring. E. coli ST302 (O108:H9, O182:H9, O45:H9) are aEPEC that have been isolated from diarrheic human, pig and rabbit hosts, as well as in healthy pigs, however no study to date has focused on E. coli ST302 strains. Through WGS and hybrid assembly we present the first closed chromosome, and two circularized plasmids of an ST302 strain - F2_18C, isolated from a healthy pig in Australia. A phylogenetic analysis placed E. coli ST302 strains in proximity to EHEC ST32 (O145:H28) strains. Public databases were interrogated for WGSs of E. coli ST302 strains and short-read gene screens were used to compare their virulence-associated gene (VAG) and antimicrobial resistance gene (ARG) cargo. E. coli ST302 strains carry diverse VAGs, including those that typically associated with extraintestinal pathogenic E. coli (ExPEC). Plasmid comparisons showed that pF2_18C_FIB shared homology with EHEC virulence plasmids such as pO103 while pF2_18C_HI2 is a large multidrug resistance IncHI2:ST3 plasmid. A comparison of 33 HI2:ST3 plasmids demonstrated that those of Australian origin have not acquired resistances to extended-spectrum beta-lactams, colistin, fosfomycin or rifampicin, unlike those originating from Asia. F2_18C was shown to carry two additional pathogenicity islands – ETT2, and the STEC-associated PAICL3, plasmid-associated heavy metal resistance genes, as well as several unoccupied stx-phage attachment sites. This study sheds light on the virulence and AMR potential of E. coli ST302 strains and informs AMR genomic surveillance.